Penerapan Standar Pelayanan Ombudsman RI Sulawesi Selatan Dalam Menangani Pengaduan Masyarakat - Aulianti Marham; Firman Umar; Herman Herman (Jurnal Tomalebbi, 2025)
This study aims to determine the implementation of Ombudsman service standards in handling public complaints in Makassar City and to identify the challenges encountered during their implementation. The data collection method involved direct interviews with staff in the report reception, report examination, prevention, and service user communities, as well as documentation in the form of data collection from service standard billboards and photographs of the research location's conditions. The data obtained from the results of this study were processed using descriptive qualitative data analysis. The results of the study show that: Based on the six components of service standards according to Permen PAN-RB Number 15 of 2014, the results of the study show that (1) the South Sulawesi Representative of the Republic of Indonesia Ombudsman has implemented effective, open, and responsive service standards, including administrative requirements, complaint systems and mechanisms, free service fees, structured completion periods, transparent service products, and organized complaint handling. (2) Challenges in the form of limited human resources and obstacles to the direct examination process to the reported agency caused by the blocking of the field investigation budget. These obstacles result in the examination and complaint resolution process being less than optimal and have an impact on the speed of service.